Collaboration in times of COVID-19: the urgent need for open-data sharing in Latin America - Curioso, Walter H. (2020)
The pandemic of COVID-19 has shown that the information disseminated through peer-reviewed journals and accompanying online data sets is vital for decision-makers. However, we are currently seeing several deficiencies in open-data sharing mechanisms globally, and in particular Latin American countries, and therefore, this highlights the need for open access to data. Latin American and Caribbean countries have remarkable initiatives to publish ‘open-access’ science through the Scientific Electronic Library On-line (SciELO),1 comprising a network of 16 national open-access journal collections and included more than 1350 active titles. The SciELO collections publish the best journals from the most research-productive countries from Latin America and the Caribbean region. Moreover, the ‘LA Referencia’2 is a Latin American network of 10 countries whose open-access repositories share interoperability standards with the objective to share and give visibility to the scientific production of higher education institutions and scientific research in Latin America. This initiative provides access to more than one million scientific articles, 800 000 graduate theses and more than 57 000 reports from more than 210 universities and institutions in Latin America. The COVID-19 response requires an integrative, collaborative and managing real-time deidentified data and information to produce the best decision-making.3 Following the interoperable collaboration model for sharing journals, thesis and reports in Latin America, we urgently need interoperable, open-data repositories.4 We still need to solve the technological, policy/legal, financial/economical, organisational and sociocultural challenges that limit the open access to data and open government data initiatives,5 including the cultural resistance of sharing data as is still observed in Peru and other countries in Latin America. While there are some efforts of global data repositories6 and recent initiatives to open individual-level data such in Mexico, Colombia and Peru,7 there is still a lack in demographics and operational information, such as number and types of tests (molecular and/or antibodies), hospital beds, intensive care units, case definitions and so on. Even more critical, within each country, the availability of information regarding the aforementioned variables and population composition is highly heterogeneous between urban and rural areas, increasing the uncertainty and hampering the timely response required during this pandemic. Local, regional and national governments play a key role in this pandemic, and we need to integrate efforts from academia, civil society and the private sector.8 The lack of funding to strengthen health information systems and information interoperability,9 and bureaucratic barriers to exchange information, move towards open data will be essential to face this pandemic, contributing to better transparency, reproducibility of results and evidence-based decision-making.